THE PROBLEMS OF IMPLEMENTATION AND REGULATION OF LAND MARKET IN THE AGRICULTURAL SECTOR OF UKRAINE - Anatoliy SHVORAK; Dmytro FILIUK; Nataliia KORETSKA; Nataliya VAHNOVSKA; Iryna BRODSKA; Alla TENDYUK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the article it is proved that the current situation in conducting agrarian reform in Ukraine is characterized by the formal completion of the restructuring of collective farms and the conclusion of the final stage of privatization of agricultural land. However, the main feature of this period is that the initiative in the development of reform has shifted from the state to agribusiness. So, if in the process of reform the state initiated the restructuring of collective agricultural enterprises, offered their organizational and legal forms, then in the pre-reform period, this initiative went to agribusiness, the manifestation of which was the emergence of agroholdings. Also the article analyses preventive measures during proceedings of land market in the countries of Europe, Argentine and the existing state of land relations in Ukraine. The study substantiates that in Ukraine emergence of agroholdings it is connected with imperfection and failures in functioning of economy, the lack of necessary institutional and legal conditions for conducting effective business inadequate the policy of the state, in particular lack of the full market of the farmland. In the article we have proved that consolidation of the agricultural land by agroholdings by replacement from the market of land lease of a certain number of the agrarian enterprises and farmers creates a certain negative social and economic situation in the village. It is proved that the introduction of the land market should not be an end in itself, but must obey the purpose of successful development of the agricultural sector on the basis of national SME based on organic farming and will revive the Ukrainian agriculture, to create appropriate social living conditions in rural areas to make the country prosperous.